Impact of spleen preservation on the incidence of postoperative pancreatic fistula after distal pancreatectomy: Is less more? - Şandra-Petrescu, Flavius Ionuţ; Tzatzarakis, Emmanouil; Mansour Basha, Mamdouh; Rückert, Felix; Reißfelder, Christoph; Birgin, Emrullah; Rahbari, Nuh Nabi (Pancreatology, 2022)
Background - Postoperative pancreatic fistula (POPF) remains a major complication after distal pancreatectomy (DP) with a significant impact on patients’ quality of life. There is limited evidence that preservation of the spleen reduces the risk of POPF. Therefore, we aimed to investigate the impact of splenectomy on perioperative outcome. - Methods - Data from patients who underwent DP for malignant and benign disease at our institution between 2004 and 2021 were reviewed. Patients were grouped according to spleen preservation (SP-DP) and splenectomy (DPS). Intraoperative parameters and postoperative outcomes were compared between groups. Univariable and multivariable analyses were used to investigate factors that influence the occurrence of clinically relevant (cr)POPF. - Results - A total of 199 patients were included, of whom 61 (30.7%) patients underwent SP-DP. Patients who underwent SP-DP had a significantly lower rate of crPOPF (p = 0.022), shorter hospital stay (p = 0.003), and less readmissions (p = 0.012). On multivariate analysis, obesity (OR 2.88, p = 0.021), benign lesions (OR 2.35, p = 0.018), postoperative acute pancreatitis (OR 2.53, p = 0.028), and splenectomy (OR 2.83, p = 0.011) were independent risk factors associated with the onset of crPOPF. - Discussion - Preservation of the spleen reduces the risk of crPOPF in patients undergoing distal pancreatectomy for benign and malignant disease.